“We have been depriving them”: examining the sense of coherence of clinical staff as they implement skin-to-skin contact - Kajsa Brimdyr; Scovia N. Mbalinda; Anna Blair; Karin Cadwell (Frontiers in Global Women's Health)
BackgroundSkin-to-skin contact (SSC) immediately after birth, when the newborn baby and mother remain together during the first hour after birth, has positive health effects on the dyad's physical and emotional wellbeing; however, implementation, the purview of the hospital's labor and birthing unit staff, has been a challenge in many settings.ObjectiveTo investigate Antonovsky's salutogenic theory's sense of coherence (SOC) of birthing staff members before and after implementing skin-to-skin contact immediately after birth in a regional referral hospital in Uganda.MethodThis qualitative study explored and analyzed before-and-after interviews of clinical staff regarding their experience of practice change to immediate, continuous, and uninterrupted skin-to-skin contact for at least the first hour after birth. The semistructured interviews took place at a regional referral hospital in Western Uganda. Using thematic analysis, the interviews were analyzed for the three components central to SOC: whether the proposed change in practice (pre-SSC intervention) and experience of the change in practice (postintervention) was comprehensible, manageable, and meaningful.ResultsAn analysis indicated a high level of SOC before the intervention in relation to the meaningfulness and comprehensibility of SSC, with concerns about manageability. An analysis of postintervention interviews indicated a high level of SOC for all three aspects.ConclusionWe postulate that a high level of sense of coherence for hospital staff both before and after an intervention may play a role in successfully implementing immediate, uninterrupted skin-to-skin contact in the first hour after birth. Skin-to-skin contact immediately after birth has life-long consequences for the emotional wellbeing of both the mother and the newborn.